China's new town movements since 1949: A state/space perspective. (January 2022) - Wang, Lili
Highlights: Provides a historical review of China's three generations of new towns since 1949. Illustrates how China's new town movements are essential state strategies and projects in different periods. Reveals the continuities and changes in China's new town movements. Characterizes the "new town syndrome" and provides a critique of China's new town models. Abstract: The remarkable growth of new towns in China in the past two decades has amazed the world. How shall we make sense of these mushrooming megaprojects, which profoundly reshape the social and economic landscape not only within China but also globally? Successive reports of epic failures – with many projects evolving into ghost towns – further obscure the picture. Existing literature has been useful in highlighting the political-economic logic behind China's new town frenzy, attributing the latter to China's marketization, decentralization, and globalization. These accounts, however, focus mostly on the recent past. Lacking a truly longitudinal approach, they tend to lose sight of the underlying links between the socialist past and the postsocialist present. This paper offers a relatively holistic historical review of China's three new town movements since 1949. While problematizing these historical processes, the paper draws insights from the theory of new state spaces, viewing new town development as a distinctive spatial strategy and project of the state to facilitate accumulation, social regulation, and state-building during specific historical periods. Based on such theoretical constructs, the paper reveals the historical trajectory and patterns of China's new town movements in the past seven decades.